Implementation of two‐dimensional L‐COSY at 7 tesla: An investigation of reproducibility in human brain. Issue 6 (22nd November 2013) - Verma, Gaurav; Hariharan, Hari; Nagarajan, Rajakumar; Nanga, Ravi P.R.; Delikatny, Edward J.; Albert Thomas, M.; Poptani, Harish
<x xml:space="preserve">Abstract</x> Purpose To evaluate the utility of two‐dimensional (2D) Localized Correlated Spectroscopy (L‐COSY) in metabolic profiling of the human brain at 7 Tesla (T). Materials and Methods The 2D L‐COSY sequence was implemented at 7T and its reliability was assessed by test–retest studies of a metabolite phantom and a healthy volunteer. L‐COSY data were acquired from the occipital lobe of healthy subjects (n = 6; all male; age, 30–72 years) to assess intersubject variability. Additionally, two subjects underwent scans from the parieto‐occipital region, basal ganglia, frontal lobe or dorsolateral prefrontal cortex to test the versatility of L‐COSY in studying differing anatomy. Integral/volume measurements of L‐COSY spectra were used to estimate normalized metabolite‐to‐creatine concentrations. Results Phantom test–retest studies revealed coefficients of variation (CVs) of 3–20% for most metabolites. Human 2D L‐COSY spectra permitted detection of several metabolite resonances from multiple locations and inter‐subject variation studies demonstrated CVs of 4–26%. Cross‐peaks from gamma‐aminobutyric acid (GABA), isoleucine (Ile), lysine (Lys) and Ethanolamine (Eth) were quantified, which are not readily resolvable with conventional one‐dimensional (1D) MR spectroscopy. Conclusion 2D L‐COSY at 7T demonstrated improved sensitivity in detecting additional metabolites with reliability comparable to established techniques at lower fields, which may aid in the metabolic assessment of diseased states. J. Magn. Reson. Imaging 2014;40:1319–1327. © 2013 Wiley Periodicals, Inc.